Effect of urea molasses straw, urea treated straw and silage in the diets on growth performance of goats (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
The experiment was conducted with a view to investigate the effect of urea molasses straw (UMS), urea treated straw (UTS) and silage in the diets on growth performance of goats in Subornochar upazilas of Noakhali district. Total DM intake was significantly (P